"What Kind of Catholic Are You?" Reflexivity, Religion and Activism in the Peruvian Andes - Olson, Elizabeth 1979- (2008)
This paper explores the intersections between feminist conceptions of reflexivity and activism in the context of social research on religion in the southern Andes of Peru. Emerging geographies of religion have been strongly influenced by feminist theory and methodology, yet few geographers working on themes of religion have openly analysed the role of reflexivity in research or activism. I draw upon the research that I conducted with the Catholic Iglesia Surandina and the Protestant Iglesia Evangélica Peruana in one of the high provinces of Cusco, and consider two different approaches toward reflexivity—a focus on my own religious identity and considerations of access, and a broader engagement with the politics of knowledge construction in the region. I conclude by suggesting the need for a more thoughtful consideration of the complex and contradictory politics and ethics of social religious research.
Keywords: Peru; Feminist Theory; Methods; Normativity; Reflexivity; Religion